The Existence of the Kejei Dance of the Rejang Tribe as an Educational Dance Through the Selupu Rejang Art Community - Bunga Naselia; Daryusti Daryusti; Agusti Efi (International Journal of Educational Dynamics, 2021)
This study analyzes community participation in preserving the existence of the Kejei dance culture of the Rejang tribe through the arts community in the Selupu Rejang sub-district, Rejang Lebong Regency, Bengkulu Province. This research is qualitative. Methods of collecting data using research observations, interview methods, and documentation. The interview technique was carried out in an unstructured manner using interview guidelines. Research data analysis is descriptive. The results of data processing in this study show that efforts to preserve the Kejei dance of the Rejang tribe through the art community in the Selupu Rejang sub-district use three methods, namely protection efforts are an effort to maintain the existence of the Kejei dance so that it does not become extinct by conducting dance training Kejei every week regularly. Development efforts are carried out through the quantity aspect of the dance, namely the development of the number of actors (dancers), the number of users, and the number of regions that receive the Kejei dance. Third, efforts to utilize the Kejei dance as an effort to introduce the Kejei dance to the wider community that the Kejei dance must be maintained.